KINERJA SATUAN POLISI PAMONG PRAJA DALAM MENERTIBKAN PEDAGANG KAKI LIMA DI KOTA PEKANBARU - Ainun Zakiyah; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
The problem of street vendors in Pekanbaru City that has not been resolved is a dilemma. The presence of street vendors who are in places not intended for them, always causes problems with urban planning and disturbance of public order. Control for the sake of control has often been carried out by the Civil Service Police Unit of the City of Pekanbaru which is a supporting element for the task of the local government in securing and implementing local government policies that are specific in the field of public order. This study aims to describe and analyze performance as well as identify and analyze factors that impede the performance of the Civil Service Police Unit in Controlling Street Vendors in Pekanbaru City. This study uses the theory of Agus Dwiyanto (2008) which uses indicators, namely: Productivity, Service Quality, Responsiveness, Responsibility, and Accountability. The research method used is a qualitative method with a phenomenological approach and is descriptive in nature. The results of the study show that the performance of the Civil Service Police Unit in Pekanbaru City is still not good. This is due to the Productivity of the Satpol in carrying out the enforcement which does not have a special controlling schedule for street vendors, the existing schedule is for patrols only. The quality of Satpol PP services in controlling street vendors is good, this is based on human resources in Satpol PP being educated or training, so they are familiar with their respective duties and functions, the Responsiveness of Satpol PP in controlling street vendors in Pekanbaru City has fulfilled the needs of street vendors, it can be seen that the Satpol provides time and place arrangements for street vendors, the Responsibility of the Civil Service Police Unit in controlling street vendors in Pekanbaru City in terms of law enforcement or sanctions is still low, the Accountability of the Civil Service Police Unit in controlling street vendors in Pekanbaru City are good. This is based on performance planning in accordance with the realization of the work program. Obstacles experienced by Satpol PP in controlling street vendors are the lack of personnel during the control process, lack of infrastructure in controlling street vendors, and lack of awareness of street vendors, especially in terms of regulation and law.